QKI-6 Suppresses Cell Proliferation, Migration, and EMT in Non-Small Cell Lung Cancer - Zhang, Haihua; Li, Junqiang; Tian, Feng; Su, Xuan; Wang, Xinxin; Tang, Di; Zhang, Lei; Zhang, Tao; Ni, Yunfeng (Frontiers in Oncology, 2022)
The RNA-binding protein quaking homolog 6 (QKI-6) is a tumor-suppressor gene in several cancers. However, its role in non-small cell lung cancer (NSCLC) is unclear. In this study, we aimed to determine the association between QKI-6 expression and survival and clinicopathological features in patients with NSCLC and identify the related mechanisms. Western blot and immunohistochemistry (IHC) were used to detect QKI-6 expression in NSCLC. The effect of QKI-6 on NSCLC cells was determined by overexpression and knockdown assays, and label-free quantitative proteomics and Western blot were used to identify the underlying mechanisms. Low QKI-6 expression level was positively correlated with poor overall survival in patients with NSCLC. Furthermore, QKI-6 overexpression inhibited NSCLC cell proliferation and migration and induced a block in the G0/G1 phase, and QKI-6 downregulation increased proliferation and migration. QKI-6 inhibited EMT processes via EGFR/SRC/STAT3 signaling by upregulating AGR2. In conclusion, QKI-6 could be used to develop novel strategies for the treatment of NSCLC.